Pyruvate as a Potential Beneficial Anion in Resuscitation Fluids - Zhou, Fang-Qiang (Frontiers in Medicine, 2022)
Fluid debates have been continuing because each of current products has its own disadvantages. The debate essentially reflects an embarrassing clinical status quo that all fluids are not quite ideal in most clinical settings. Hence, a novel fluid that overcomes most fluid defects is warranted for most patients, particularly in diabetes and elders. Pyruvate is a natural potent anti-oxidative/nitrosadive and anti-inflammatory agent. Exogenous pyruvate as an alkalizer can increase cellular hypoxia and anoxia tolerance with preservation of classic glycolytic pathways and reactivation of pyruvate dehydrogenase activity to promote oxidative metabolism and reverse the Warburg effect, robustly preventing and treating hypoxic lactic acidosis that is one of fatal complications in intensive care unit patients. Pyruvate protects multi-organ function, especially heart, brain, kidney and intestine in animal studies and clinical reports, promising greatly improve patient survival. Pyruvate-enriched fluids including crystalloids and colloids as well as oral rehydration solution (ORS) may be ideal due to pyruvate unique beneficial properties in comparison with anions in current fluids: acetate, bicarbonate, chloride, citrate, lactate and even malate. Preclinical studies demonstrate that pyruvate-enriched saline is superior to 0.9% sodium chloride; pyruvate-enriched Ringer’s solution is advantageous over lactated Ringer’s solution; further, pyruvate as a carrier in colloids like hydroxyethyl starch 130/0.4 is more beneficial than commercial counterparts and the same is pyruvate-enriched ORS more favorable than WHO-ORS in organ protection and shock resuscitation. Critical concerns must be first paid how to improve the (ab)normal saline by pyruvate for ICU patients. There were many clinical tests with a large dose of intravenous or oral pyruvate over the past half century. Results indicated its effectiveness and safety in humans. The long-term stability of pyruvate aqueous solutions and para-pyruvate cytotoxicity are not a limitation for pharmaceutical manufacturing pyruvate-enriched fluids for ICU patients. Clinical trials with sodium pyruvate-enriched solutions are urgently warranted.